2010
DOI: 10.1016/j.bbmt.2009.09.023
|View full text |Cite
|
Sign up to set email alerts
|

T helper17 Cells Are Sufficient But Not Necessary to Induce Acute Graft-Versus-Host Disease

Abstract: T helper (Th)1 cells were considered responsible for the induction of graft-versus-host disease (GVHD), but recently the concept has been challenged. Th17 cells play a critical role in mediating autoimmune diseases, but their role in the pathogenesis of GVHD remains unclear. Herein we compare the ability of in vitro generated Th1 and Th17 cells from C57BL/6 mice to induce GVHD in lethally irradiated BALB/c recipients. Allogeneic Th17 cells had superior expansion and infiltration capabilities in GVHD target org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
2
2

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 35 publications
8
69
2
2
Order By: Relevance
“…Several mouse model experiments have revealed that transfer of IL-17-producing cells induced acute GVHD, [33][34][35] whereas in contrast there is a report 31 showing that donor IL-17-producing cells ameliorated acute GVHD. Host DCs are critical in the initiation of acute GVHD, [52][53][54] leading to a hypothesis that IL-17-producing cells could modify the function of host DCs through unknown mechanisms.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several mouse model experiments have revealed that transfer of IL-17-producing cells induced acute GVHD, [33][34][35] whereas in contrast there is a report 31 showing that donor IL-17-producing cells ameliorated acute GVHD. Host DCs are critical in the initiation of acute GVHD, [52][53][54] leading to a hypothesis that IL-17-producing cells could modify the function of host DCs through unknown mechanisms.…”
Section: Discussionmentioning
confidence: 91%
“…[21][22][23][24][25][26][27][28][29] Moreover, several reports have so far shown that Th17 cells and IL-17 has a significant impact on the development of acute GVHD in mouse models. [30][31][32][33][34][35] Recent reports have shown association of SNPs in the IL-17 gene with autoimmune diseases such as rheumatoid arthritis and ulcerative colitis. [36][37][38][39] The promoter SNP of the IL-17 gene, rs2275913 (G197A), was found to be associated with the susceptibility of rheumatoid arthritis in the Norwegian population 38 as well as that of ulcerative colitis in the Japanese population.…”
Section: Introductionmentioning
confidence: 99%
“…7 We hypothesized that Th17 cells could preferentially accumulate within the target tissues of aGVHD. Thus, gastrointestinal biopsies obtained from a cohort of 23 allo-SCT patients (n ¼ 5 without and 18 with histologically proven GI aGVHD taken before starting corticosteroids) were analyzed for Th17 cell infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…Some data suggested that interleukin (IL)-17 is protective, 5 while others indicated a pathogenic role. 6,7 Of note, transplantation of Th17 cells caused lethal GVHD hallmarked by extensive tissue damage. 8 Finally, blockade of both Th1 and Th17 differentiation is required to prevent GVHD in mice.…”
Section: Introductionmentioning
confidence: 99%
“…The role of IL-17-producing Thelper cells is increasingly being recognized in GvHD. [63][64][65][66][67] Tournadre et al 68 recently showed by analyzing muscle biopsies of patients with inflammatory myopathies that IVIG could mediate their immunomodulation by acting on the Th17 pathway. One could speculate that IVIG exert their modulatory effect on GvHD by impairing the Th17 pathway, although more analysis on other Th17-family cytokines and on the nature of IL-17 secreting cells in our model will be required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%